(untitled) (Sirte University Journal of Humanities, 2026)
This study analyzes the legal framework governing electronic money laundering within Libyan legislation, framing it as a critical transnational threat to national security and the economy. The research evaluates enforcement and prevention mechanisms under Resolution No. 1013 of 2017 and the subsequent Cybercrime Law No. 5 of 2022, which addresses the evolution of these crimes into digital formats. Adopting a systematic methodology, the study defines the crime’s nature and elements before examining its socioeconomic impacts and existing combat strategies. Given the scarcity of academic literature on this topic in Libya, this research provides significant scientific value. It serves as a vital guide for policymakers to enhance legal protections against increasingly sophisticated laundering techniques. Ultimately, the findings highlight the necessity of aligning national laws with international efforts to mitigate the growing dangers of the digital financial era.